DESIGN ASPECT OF NITROBENZENE PRODUCTION - Agustriyanto, Rudy (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
Study on process design of benzene nitrification has been done. The activation energy (Ea) and frequency factor (k0) for this reaction were obtained from the literature. Calculation of physical and chemical properties was conducted automatically in HYSYS using NRTL and UNIQUAC Thermodynamic model. Several aspects of process design were investigated during simulation, i.e., the dependence of reaction conversion to temperature, the effect of sulfuric acid ratio against nitric acid in the synthesis of nitrobenzene in CSTR (Continuous Stirred Tank Reactor), and the effect of reactor series and parallel structure to reaction conversion. The highest conversion that can be achieved in single CSTR amounting to 96.9% at a ratio of sulfuric acid to nitric acid = 3.5, and temperature of 50 ºC. However, based on this study it is recommended that the most favorable condition for the nitration of benzene in an isothermal CSTR is 50 ºC operating temperature and a low ratio of sulfuric acid to nitric acid (i.e., 2.5 – 3).